2018
DOI: 10.1097/rct.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

The Value of 16-cm Wide-Detector Computed Tomography in Coronary Computed Tomography Angiography for Patients With High Heart Rate Variability

Abstract: Single-heartbeat free-breathing CCTA can be performed for patients with high HRv using 16-cm wide-detector CT scanner to achieve diagnostic image quality with low radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, we have conducted subgroups analysis based on HR and we proved that the low contrast dose protocol we proposed in this study could be applied to patients with both average HR and high HR. High HR has been criticized for degraded image quality in CCTA examination, which has raised a signi cant concern [21][22][23][24] in recent years. Compared to patients with regular HR, CCTA images of patients with high heart rates suffer from motion artifacts due to their uneven ratio of systolic to diastolic phases and their excessive motion velocities that exceed the temporal resolution of the CT scanners.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have conducted subgroups analysis based on HR and we proved that the low contrast dose protocol we proposed in this study could be applied to patients with both average HR and high HR. High HR has been criticized for degraded image quality in CCTA examination, which has raised a signi cant concern [21][22][23][24] in recent years. Compared to patients with regular HR, CCTA images of patients with high heart rates suffer from motion artifacts due to their uneven ratio of systolic to diastolic phases and their excessive motion velocities that exceed the temporal resolution of the CT scanners.…”
Section: Discussionmentioning
confidence: 99%
“…be as large as possible to allow the study of the entire cardiac area in the smallest number of heart cycles 35) .…”
Section: Cardiac Petmentioning
confidence: 99%
“…The motion velocity and path of coronary arteries from adjacent cardiac phases are characterized, and the information is used to calculate an optimal estimation of the vessel lumen at the target phase by the snapshot freeze (SSF) reconstruction technique (GE Healthcare) (29). Several previous studies reported that the SSF technique improves diagnostic accuracy using a 64-row detector CT scanner (29)(30)(31), and this technique is currently available on wide-detector CT scanners (32)(33)(34).…”
Section: Effect Of Heart Rate and Image Qualitymentioning
confidence: 99%
“…In the 16-cm wide-detector CT scanner of GE Healthcare (Revolution CT), using the one-beat auto-gating technique to identify the ideal time within one cardiac cycle at any heart rate in combination with the SSF motion correction kjronline.org technique can achieve coronary artery images with diagnostic quality even in patients with a high heart rate or high heart rate variability (32)(33)(34).…”
Section: Effect Of Heart Rate and Image Qualitymentioning
confidence: 99%